2018
DOI: 10.1186/s12885-018-4747-1
|View full text |Cite
|
Sign up to set email alerts
|

Low level of isocitrate dehydrogenase 1 predicts unfavorable postoperative outcomes in patients with clear cell renal cell carcinoma

Abstract: BackgroundThe purpose of this study was to investigate the role of isocitrate dehydrogenase 1 (IDH1) expression on prognosis of patients with clear cell renal cell carcinoma (ccRCC) following nephrectomy.MethodsWe retrospectively enrolled 358 ccRCC patients undergoing nephrectomy in Renji Hospital. Clinicopathologic features, overall survival (OS) and recurrence-free survival (RFS) of ccRCC patents were all collected. IDH1 expression level was assessed by immunohistochemistry and its association with clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…129 Specially, studies also found that IDH1 is significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared with normal kidney cells, suggesting that IDH1 may function as a candidate tumor suppressor for ccRCC. 130,131 Most studies indicate that IDH2 is also significantly upregulated in ESCC, 132 ovarian cancer, 133 lung cancer and other types of cancer, 134 playing a pro-oncogenic role. Overexpression of IDH2 decreases ROS levels and increases cancer cell growth.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…129 Specially, studies also found that IDH1 is significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared with normal kidney cells, suggesting that IDH1 may function as a candidate tumor suppressor for ccRCC. 130,131 Most studies indicate that IDH2 is also significantly upregulated in ESCC, 132 ovarian cancer, 133 lung cancer and other types of cancer, 134 playing a pro-oncogenic role. Overexpression of IDH2 decreases ROS levels and increases cancer cell growth.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
“… 129 Specially, studies also found that IDH1 is significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared with normal kidney cells, suggesting that IDH1 may function as a candidate tumor suppressor for ccRCC. 130 , 131 …”
Section: Molecular Mechanisms Of Nadph Homeostasis In Cancermentioning
confidence: 99%
“…Alterations in genes ( SDHB ) encoding yet another TCA cycle enzyme, succinate dehydrogenase, have been reported in patients with hereditary paragangliomatosis with phaeochromocytomas and in some ccRCC cases [6]. Additionally, low expression of isocitrate dehydrogenase (IDH1) was recently reported to be associated with poor prognosis in ccRCC [7]. Isocitrate dehydrogenase catalyzes the conversion of the TCA intermediate isocitrate to α-ketoglutarate (alphaKG).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the expression of miR-30c-5p in RCC is downregulated which would suggest an upregulation of IDH's mRNA expression. However, this protein was shown to be downregulated in this tumor model [85]. In fact, a single mRNA can be regulate by several miRNAs, making the miRNA:mRNA expression not always inversely correlated.…”
Section: Krebs Cyclementioning
confidence: 81%